LANGUAGE AND SOCIAL DEVELOPMENT OF CHILD THROUGH PARENTAL STIMULATION: A CASE STUDY - Nasution, Ninda Yustika; Listiana, Aan (Esteem Journal of English Education Study Programme, 2025)
The purpose of this research is to investigate the relation between the stimulation of play that is provided by parents and the development of linguistic and social skills in young children. One of the most important methods in which children develop their social, emotional, and cognitive abilities is through play. The purpose of this study was to identify different types of play, such as physical, symbolic, and social play, as well as the role that parents play in supporting these types of play. This was accomplished through observations, interviews with parents, and documenting of play activities. According to the findings, parents who are actively involved in play with their children have the ability to improve their children's social skills, including the ability to share, cooperate, resolve conflicts, and understand diverse points of view. In addition, it was discovered that play stimulation, particularly in the form of role-playing and group play, plays a significant role in the development of empathy, communication skills, and language acquisition. The excessive use of digital media and the restricted amount of time that parents have available to spend with their children were highlighted as variables that inhibit the quality of interactions that occur during play. The findings of this study indicate that parental play stimulation is an essential component in the process of nurturing both social and language development in young children. This finding has implications for both parents and educators in terms of the development of play activities that support children's overall growth and development.